Determination of boron in various types of pasta using ICP-OES and UV/VIS spectrophotometry / Nik Nur Syazwani Nik Yahya - Nik Yahya, Nik Nur Syazwani (Faculty of Applied Sciences, 2009)
This study analyzed boron content in commonly pasta such as spaghetti and macaroni. Boron content was analyzed based on 6 different brands of spaghetti and macaroni. This was done by using two different instruments and methods which is Inductively Coupled Plasma Optical Emission Spectroscopy and UV Visible Spectrophotometry. In spaghetti samples, the highest amount of boron concentration was obtained in brand B which is 0.034±0.005 ppm by ICP-OES and 11.90±0.68 ppm by UV/Vis. For macaroni samples, brand A contains the highest amount of boron concentration which is 0.028±0.005 ppm measured by ICP-OES and 11.44±0.1Q ppm by UV/Vis. From the results obtained by these two instrument, boron concentration measured by ICP-OES is much lower than UV/Vis. This is because ICP-OES is not sensitive enough to detect boron in low concentration and their accuracy is less compared to UV/Vis. Thus, the best method for determining boron is by using azomethine-H which use UV/Vis.